(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The critical analyses of the various representations ofthe partition violence attempted in the preceding section clearly reveal in theobsessive nature of the event of vivisection of India in 1947. The event andthe concomitant unprecedented carnage witnessed by the subcontinent came as ashockingly ironic reward of the united fight for freedom. The partitionfiction, therefore, is a brutally realistic account of the blood curdlingviolence. However, it would be injudicious to infer that thepartition novels considered in the study are mere stories of the harrowingincidents of violence. Instead, they are, in essence, discerning insights intothe complex human nature. What Harish Raizada observes of Khushwant Singh isequally true of all other Indo-English novelists whose fiction has treated theholocaust of partition, Raijada writes that Khushwant Singh turned to fiction “tolet out his disenchantment with the long-cherished human values in the wake ofinhuman bestial horrors and insane savage killings on both sides during thepartition of the sub-continent between India and Pakistan in August 1947....”1